Business Regulation Operational Guide - World Bank (Washington, DC, 2022)
The private sector has been at the forefront of economic transformation, job creation, and poverty reduction around the world for the past three decades. In developing countries, the private sector provides over 90 percent of jobs. According to a World Bank Group survey of the poor getting a job or starting a business is the most effective way out of poverty. As the global economy seeks to repair the economic scars from the COVID-19 pandemic, with strained public resources, countries will have to rely even more on the private sector to mobilize the investment needed for recovery. The World Bank Group Investment Climate (IC) team works with regional teams and client countries to develop regulatory reform programs to support private sector development in five workstreams. The areas of work include identifying and designing reforms to improve the regulatory environment for firms along all phases of the business life cycle - formalization and entry, operations, expansion, and exit. Investment Climate programs are implemented through the full range of WBG instruments, both lending and advisory. This guide provides a framework for policy makers and economic development practitioners to use to design effective regulatory reforms addressing the entire life cycle of a firm. In all areas of regulation, the IC team emphasizes the equal importance of refining the rules to create a foundation for reform and improving implementation to provide a truly level playing field for businesses.